The Past and the Present of the Irish Neutrality - Labáth, Ádám (POLARITIES, 2025)
Irish neutrality is rooted in the ages of the colonialism and the rise of the Irish national movements, and has become synonymous with the concepts of sovereignty and national identity. This article aims to understand the Irish neutrality historical and social background and to introduce the current debates about the future. As in many European neutral states, the argument about the neutrality has intesified in Ireland as well. Today, Irish neutrality can be marked by contradictions, since Ireland is an integral part of the European integration, advocates for other national and freedom movements, pledges solidarity with other postcolonial and opressed groups, while the Irish society sticks to neutrality, as a national treasure. Today’s geopolitical events also impacting the Irish neutrality, and the question remains: Is Ireland heading toward the closer European defense integration or toward the committed neutrality.